PLIGHT OF FEMALE DOMESTIC WORKERS IN INDIA: DEVELOPMENT OF A CONCEPTUAL FRAMEWORK - Maumita Roy; Gayatri Sawant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is a country with 698.29 million of female population as per CNN, 32.8% of which are engaged in labor force according to Directorate General of Employment. A major chunk of this population are employed as domestic workers. Although the official estimate of domestic worker population is 4.2 million the actual figures are even more than 50 million. It is estimated that around three fourth of this population are women (Ghosh, 2013). In the current age urban middle-class segment are the major recruiters of domestic workers as these workers have become the backbone of their smooth day to day life (Otso Harju, 2017). Usually, domestic workers are employed on part-time, full time or round-the-clock basis. As the domestic workers are engaged in household work like cooking, cleaning etc., this is not considered as a skilled job. Primarily, illiterate and semi-literate women engage in domestic work even without substantial rights and benefits (Sandhya S. J, 2019). On one hand it contributes a lot to women empowerment and financial independence; on the other hand, domestic work being an informal sector, witness challenges of low wage, long hours of work, frequent change in nature of job etc. (Baboo; Panwar, 1984). Research done on “Minimum wages for domestic work” put on record that, social understanding of household work was the critical factor in understanding the state’s response in understanding the issues faced by the domestic workers apart from labour market issues that govern legislative interventions (Neetha, 2013). In this regard, the current study focuses on an objective review of various literature which attempts to highlight the current status of females engaged in domestic work sector so that it can pave ways to bridge the inherent gaps and exploring the feasibility of bringing this sector into the organized format.